Are there multiple scaling regimes in Holocene temperature records? - Nilsen, Tine; Rypdal, Kristoffer; Fredriksen, Hege-Beate (Copernicus GmbH, 2015)
The concept of multiple scaling regimes in temperature time series is examined, with emphasis on the question whether or not a mono-scaling model can be rejected from the data at hand. A model with only one regime is simpler and is preferred if this 5 explains the observed variability. Our analysis of spectra from reconstructed air temperature from Greenland and Antarctica ice cores shows that a scale break around centennial time scales is evident for the last glacial period, but not for the Holocene. Nor by analysing a number of late Holocene multiproxy temperature reconstructions can a significant scale break be identified. Our results indicate that a mono-scaling 10 model cannot be rejected as a null model for the Holocene climate up to at least millennial time scales, although it can be rejected for the glacial climate state. The scale break observed from the glacial time ice core records is likely caused by the influence of Dansgaard–Oeschger events and teleconnections to the Southern Hemisphere on centennial time scales. From our analysis we conclude that the two-regime model is 15 not sufficiently justified for the Holocene to be used for temperature prediction on centennial time scales